Diginal-Based Management Integrated With the Development of Community Education in the Maluku Islands - Abednego Abednego (Peneliti.net, 2022)
Face-to-face teaching and learning in islands, remote areas, different cultures and different age levels of students will face basic problems such as communication, transportation, high costs, bringing in qualified teachers. The e-learning system is the right strategy to overcome these problems. This study uses a qualitative approach. Data was collected through Focus Group Discussion and Semi-Structured Interviews, requiring 47 participants. Using SWOT analysis, it is most often used as a tool to analyze the internal strengths and weaknesses of the organization that can be controlled as well as external opportunities and threats that are difficult to identify (Chermack and Kasshanna, 2007; Leigh, 2010). The research findings have identified 3 important components that must be prepared for an e-learning-based learning community using ICT, namely infrastructure, human resources and applications. The future of digital-based learning management requires a long-term strategic plan that can formulate the vision, mission, goals of community education institutions